2021
DOI: 10.1063/5.0042582
|View full text |Cite
|
Sign up to set email alerts
|

Pressure gradient effect on spin-crossover materials: Experiment vs theory

Abstract: We studied the effect of a non-hydrostatic pressure on the hysteretic spin crossover in coordination complexes.By introducing into an Ising-like model a double distribution of the interactions and gap energy, respectively, we were able to generate the major hysteresis loop and the FORC diagram for spin-crossover systems of 10 6 hysterons (like-spin domains). We show that, for high pressure gradients around the spin-crossover system, the thermal hysteresis loop takes an asymmetric shape, in good agreement with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 45 publications
0
9
0
Order By: Relevance
“…Therefore, the transition becomes gradual with hysteresis. The influence of pressure on the shape of the transition loop recently has been studied in ref , and it has been shown that the gradient of the pressure results in inclined the ST loop . Here, we show that not only the pressure gradient but also the internal pressure caused by different compressibilities of HS and LS molecules are changed when the pressure variation inclines the hysteresis loop and induces the mixing intermediate state.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the transition becomes gradual with hysteresis. The influence of pressure on the shape of the transition loop recently has been studied in ref , and it has been shown that the gradient of the pressure results in inclined the ST loop . Here, we show that not only the pressure gradient but also the internal pressure caused by different compressibilities of HS and LS molecules are changed when the pressure variation inclines the hysteresis loop and induces the mixing intermediate state.…”
Section: Discussionmentioning
confidence: 99%
“…The influence of pressure on the shape of the transition loop recently has been studied in ref 50, and it has been shown that the gradient of the pressure results in inclined the ST loop. 50 Here, we show that not only the pressure gradient but also the internal pressure caused by different compressibilities of HS and LS molecules are changed when the pressure variation inclines the hysteresis loop and induces the mixing intermediate state. The difference between internal and external pressure is comparable to the difference between magnetic induction inside a magnet and an external magnetic field.…”
Section: Hs Lsmentioning
confidence: 99%
“…The FORC diagram method has been proved a very sensitive tool for the characterization of the hysteretic properties of spin transition materials as it gives more information about the spin-domain structure which influences the material's behavior inside the hysteresis loop [24,25]. Figure 7 shows the FORC diagrams obtained within the framework of the CPM where the contour plot has a circular shape and for four other values of the sample contrast parameter C, expressed in reversal-measurement temperature coordinates.…”
Section: Km Correction On the Forc Diagrammentioning
confidence: 99%
“…This aspect was recently pointed out in spin-crossover (SCO) solids, as such gradients could be a major ingredient to describe the hysteretic properties of these materials. 58 In the case of PBAs, these distortions may involve correlated tilts of the metallocyanide units, presumably at medium distances due to the inherent structural disorder, and have a large counteraction on the charge transfer processes because of a decrease of the transfer integral.…”
Section: Impact Of Inhomogeneous Stress Fieldsmentioning
confidence: 99%